Synthesis of Ligand para-di-2-(1-phenyl-3-pyridyl-4,5-dihydro-1H-pyrazol-5-yl) benzene by Aldol Condensation Method - Yulian Syahputri; Sutanto Sutanto; Linda Jati Kusumawardani (Helium: Journal of Science and Applied Chemistry, 2021)
Synthesis of pyrazoline derivative ligand para-di-2-(1-phenyl-3-pyridyl-4,5-dihydro-1H-pyrazol-5-yl)benzene has been successfully carried out by aldol condensation method using 2-acetyl pyridine and terephthalaldehyde in ethanol solution. The synthesis results are then reacted with excess phenyl hydrazine. The yield of ligand obtainedwas 63.10% of ayellow solid. The ligand was characterized using 1H-NMR spectroscopy, ultraviolet-visible (UV-Vis) spectroscopy, fourier transform infra-red (FTIR) spectroscopy and spectrofluorometer. The characterization with UV-Vis spectrophotometer results shows ligand has a large value of molar absorptivity (Îµ) at wavelength 236 nm and concentration 5x10-5 M.The results indicates that the ligand has a strong fluorescence intensity. It proved by peak emission at 467.5 nm (I = 4055 a.u).